Analysis of The Effect of Hatha Yoga on The Quality of Sleep and Immune System Among The Students in Public Health Postgraduate Program At UNNES - Nopitasari, Dewi; Sri Ratna Rahayu, Rr. (Universitas Negeri Semarang, 2018)
The sleep quality of a person is said to be good if it does not show any signs of lack of sleep and he or she has no problems in sleeping. Lack of sleep can also cause changes in cytokine tissue. So, the immune system will work less effectively. Hatha yoga exercises is one of the non-pharmacological therapy that can improve the quality of sleep and immune system. The purpose of this study is to analyze the effect of Hatha Yoga exercises on the quality of sleep and immune system.among the students in Public Health Postgraduate Program at Unnes.The method used here was quasi experiment with pretest and posttest with control group design. The population in this study was all students in Public Health Postgraduate Program at Unnes. The samples were selected based on inclusion and exclusion criteria by purposive sampling technique. The samples obtained were 24 respondents, divided into two groups to perform hatha yoga exercises in the intervention group. The study instrument used was questionnaire on the quality of sleep and leukocyte examination to find out the respondent's immunity.The study results showed that there was a significant difference in the quality of sleep between the intervention group and control group after the provision of hatha yoga exercises in intervention group with p value of 0.000 (p <0.05) and there was no significant effect on the immunity between the control group and the intervention group after the provision of hatha yoga exercises with p value of 0.092 ( p> 0.05). Conclusion: Hatha yoga exercises had an effect on the quality of sleep but hatha yoga exercises had no effect on immunity.